Effectiveness Of E-Bmd Implementation in The Context Of Presenting Financial Statements (Fixed Assets and Current Assets) at The Financial And Asset Management Agency Of Sikka District T.A. 2023 - Gita Yolanda; Emilianus Eo Kutu Goo; Maria Modesta Missi Mone (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
The implementation of the Elektronik Barang Milik Daerah (e-BMD) system is crucial for improving the management and financial reporting of regional government assets. This study examines the effectiveness of e-BMD at the Badan Pengelola Keuangan dan Aset Daerah (BPKAD) of Sikka Regency in preparing financial reports, particularly for fixed and current assets. Using qualitative methods, data were collected through interviews, observation, and document analysis. The results show that e-BMD significantly enhances efficiency, accuracy, and accountability in asset management, although technical and resource limitations remain challenges. Recommendations include training enhancement and system optimization to improve performance.